Carcass Production and Component of Lamb Provided Metanogenic Inhibitor Feed - Sondakh, E.H.B; Yusiati, Lies Mira; Suryanto, Edi; Kalele, J.A.D; Ratulangi, F.S (2015)
ABSTRACT: The aim of this research is to investigate effects using different level of medium chain fatty acids (MCFA) as methanogenic inhibitor substrate to evaluate production of carcass.Three different proportion of medium chain fatty acids, namely R0: 0% MCFA, R1: 1% MCFA, R2: 1.5% MCFA in 100% dry matter. Each treatment consisted of four sheep. The sheep were kept for three months before slaughtered. The data were analyzed using a variance analysis (completely randomized design), followed by Duncan’s new Multiple Range Test (DMRT) for the significant means. The variables measured were production of carcass consisted of body weight, carcass weight, dressing percentage, back fat thickness, lean, carcass fat and bone. The result indicated that R0, R1 and R2 treatment were not different significantly (p>0.05) on back fat thickness, lean, carcass fat and bone, meanwhile to body weight, carcass weight, dressing percentage was significantly (p<0.05). The conclusion of research was medium chain fatty acids 1 - 1.5% as metanogenic inhibitor feeds can increase the production of carcass with an increase in body weight, carcass percentage and not degrade the quality of carcass